El De Arte Gramática de G.J. Voss - Fuentes Moreno, Francisco (1994)
In this paper we try to approach the De arte grammatica and to offer an overall view of this basic work of G.J. Voss, one of the more representative figures of the Classical Scholarship in the seventeenth century.
Keywords: Vossius, Gerardus Joannes, -- 1577-1649; Humanismo